Indole-based, Antiproliferative Agents Targeting Tubulin Polymerization - Sang, Ya-Li; Zhang, Wei-Ming; Lv, Peng-Cheng; Zhu, Hai-Liang (Current Topics in Medicinal Chemistry, 2017)
Indole is a potential lead for drug design which has been found in numerous pharmaceutically important compounds due to its medicinal properties, such as anti-tumor, anti-bacterial, anti-virus and anti-inflammatory. In the last decade, interfering with microtubule polymerization, a potential orientation to cause cell cycle arrest and apoptosis has become a promising method for cancer therapy. Thus, indole-based agents capable to modulate the microtubule assembly have gained considerable interest among scientists. This review describes the synthesis, bioactivities and SARs of indole-based agents targeting tubulin polymerization during the past decade.
Keywords: Anti-tumor